Development of Environmental Education Teaching Module Using Discovery Learning Model for Elementary Students - Budiono, Hendra; Khoirunnisa, Khoirunnisa; Chan, Faizal; Roza, Mira Amelia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This study aims to produce a product in the form of an environmental education teaching module using the discovery learning model for elementary students. This research is a development research conducted using the 4D development model, which consists of define, design, develop, and disseminate. The research subjects involved teachers and students from the second-grade class of SDN 067/VIII Muaro Sekalo. Data collection techniques were the use of validation questionnaires for teacher and student responses. The collected data were analyzed using qualitative and quantitative analysis. The research results indicate the validity and practicality of the environmental education teaching module using the discovery learning model for elementary students consists of an average validity level of 4.47 with very valid category and an average practicality level of 4.81 with very practical category. It can be concluded that the development of the environmental education teaching module using the discovery learning model for elementary school students is suitable for use in the learning process.